2022
DOI: 10.3390/s22020603
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Spectral Characteristics of Dye- and Pigment-Based Inkjet Prints by VNIR Hyperspectral Imaging

Abstract: Fine art photography, paper documents, and other parts of printing that aim to keep value are searching for credible techniques and mediums suitable for long-term archiving purposes. In general, long-lasting pigment-based inks are used for archival print creation. However, they are very often replaced or forged by dye-based inks, with lower fade resistance and, therefore, lower archiving potential. Frequently, the difference between the dye- and pigment-based prints is hard to uncover. Finding a simple tool fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As depicted in Figure 10 , the spectral response of one of the leaf pairs is analyzed, which shows that a few bands are distinctively different between the printed and the real leaf. For example, the paper constituents in the printed leaf generate a notable spectral reflectance peak of around 500 nm, deviating from the spectral response of a real leaf [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Figure 10 , the spectral response of one of the leaf pairs is analyzed, which shows that a few bands are distinctively different between the printed and the real leaf. For example, the paper constituents in the printed leaf generate a notable spectral reflectance peak of around 500 nm, deviating from the spectral response of a real leaf [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is clearly shown that these bands can be used to sufficiently differentiate printed and real leaves. The synthetic RGB image for printed leaves has a diverse gradient of chromatic light reflection (refer to Figure 11 ) due to the injection of fluorescent ink on the paper [ 61 ]. On the other hand, different leaves have reflections of diverse light intensity due to the varying proportions of chlorophyll [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…It improves the spectral discriminability by making dissimilar spectra more distinctive and similar spectra more comparable. It has been used for dye and pigment in inkjet prints 27 , and for ink classification 25 .…”
Section: Sidsammentioning
confidence: 99%
“…The most common approach involves computing the average JM distance for all pairs of classes 29 . This metric has been applied to analyze dyes and pigments in inkjet prints 27 , and for ink classification 25 . In this metric, the JM and SAM algorithms are orthogonally projected by using either a sine (Eq.…”
Section: Jmsammentioning
confidence: 99%
“…A hyperspectral picture is defined as an image with a spectral resolution of 10 nm or less, whereas a multispectral image refers to an image with a spectral resolution beyond 10 nm [14]. Furthermore, it is worth noting that the spectral characteristics of substances exhibit distinctiveness, hence enabling the identification of various objects [15]. This identification process may be achieved with a high level of precision by analyzing the spectral features or spectrum responses of the object or material within the acquired hyperspectral picture.…”
Section: Introductionmentioning
confidence: 99%